Possibility of transmission of severe acute respiratory syndrome coronavirus 2 in a tertiary care hospital setting: A case study. Issue 3 (September 2020) - Morioka, Shinichiro; Nakamura, Keiji; Iida, Shun; Kutsuna, Satoshi; Kinoshita, Noriko; Suzuki, Tetsuya; Suzuki, Tadaki; Yamamoto, Kei; Hayakawa, Kayoko; Saito, Sho; Ohmagari, Norio
Summary: Introduction: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spready globally. This report describes the person-to-person transmission of the virus in a hospital setting. Presentation of case: A 63-year-old man with pneumonia and a 70-year-old man without symptoms were admitted to a tertiary hospital with SARS-CoV-2 infection. Both men were accompanied by their wives, who stayed with their husbands during their hospitalisation. The wives of Patient 1 and Patient 2 tested positive and negative for SARS-CoV-2, respectively. Of the environmental samples tested, 1/21 and 0/25 from the rooms of Patient 1 and Patient 2, respectively, tested positive for SARS-CoV-2. Patient 1's wife appeared to have acquired infection during her husband's hospitalisation. Discussion: The study had several limitations, including methodology inconsistencies. Additionally, a viral culture was not performed to demonstrate the viability of the virus identified in the environmental sample. Finally, the wife of Patient 1 stayed on the Diamond Princess cruise ship for 4 days before being transferred to the hospital and may have been infected on the ship and not while in the hospital. Conclusion: Our study suggests that airborne transmission of SARS-CoV-2 may be limited. However, owing to the abovementioned limitations, the results should be interpreted with caution.